Pengaruh Motivasi dan Komunikasi Terhadap Kemampuan Kerja dan Dampaknya Terhadap Kinerja Pegawai Allstay Hotel Semarang - Hendra Jaya; Ganda Subrata (Master Manajemen, 2023)
This research aims to determine the influence of motivation and communication on work ability and its impact on the performance of Allstay Hotel Semarang employees. The population of this research is all 59 Allstay Hotel Semarang employees. Samples were taken using the census method. Data analysis techniques use regression analysis and path analysis. The test results concluded that (1) there is a positive and significant influence of motivation and communication on work ability, (2) there is a positive and significant influence of motivation and communication on performance, (3) work ability does not mediate the effect of motivation on performance, (4) work ability does not mediate the effect of communication on performance. The suggestions given are (1) leaders should be able to strive to provide better work motivation, (2) leaders should always communicate well with subordinates